100 Women who made History Remarkable women who shaped our world - Caldwell, Stella; Hibbert, Clare; Mills, Andrea; Skene, Rona (London, Dorling Kindersley Limited, 2017)
If you thought that it was a man's world, think again! 100 Women Who Made History is the exciting story of the women who changed the world, from Anne Frank to J.K. Rowling. Meet the most talented and famous women in history, from politics, science, business, and the arts, from exciting entrepreneurs to clever creative. Discover landmark moments in the lives of amazing historical women from Joan of Arc to Marie Curie, up to and including modern game-changers such as Maya Angelou, Angela Merkel, Serena Williams, and Malala Yousafzai. With beautiful photography and fun illustrations, 100 Women Who Made History is a fascinating look at the pioneering and inspiring women in history, from ancient Greece to the present day. 100 Women Who Made History is the perfect book of history for kids aged 9 and up as they discover women who left their mark
Keywords: General History- Biography